الإلتبـاس فى لغــة القـرآن ودوره فى تعميـمـــه - M. Rasyid Ridha (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The Qur’an is the guidance for all mankind. Therefore, the Arabic language used in the Qur’an should be universal, and be easy to understand by all people. The Qur’an has beautiful, fine and standard ambiguity. Because of the ambiguity of the Qur’an language, almost all the words in the verses of the Qur’an can be interpreted. The ambiguity is one of the semantics  studies used in studying the meaning. The philosophers and the linguists employ three methods in studying the meaning, namely: 1) explaining the words naturally, 2) describing the sentences naturally, and 3) elaborating the meaning in the process of communication.   Furthermore, to elaborate the meaning, one should view it from the aspects of word, of sentence, and of what the writer and the speaker need to communicate. All the processes  of  meaning have   been applied in the Qur’an language in order to  be comprehended by people more easily.Kata Kunci : Ambiguitas, bahasa Arab, Alquran